2007
DOI: 10.1371/journal.pntd.0000083
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Blood Agar for Isolation of Mycobacteria

Abstract: Background Mycobacterium species are grown using specific media that increase laboratory cost, thus hampering their diffusion in resource-limited countries. Preliminary data suggested that versatile blood agar may be also used for mycobacterial culture.MethodologyWe examined the growth of 41 different Mycobacterium species on 5% blood agar. Over a 24-month period we analysed isolation of mycobacteria after parallel inoculation of clinical specimens into both a reference automated system (BACTEC 9000 MB broth) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 12 publications
0
38
0
4
Order By: Relevance
“…Amphotericin-B is regarded as one of the antifungal agents recommended to be added into selective media for the first isolation of Mycobacterium spp., (19), Campylobacter spp. (20), and Brucella spp.…”
Section: Methodsmentioning
confidence: 99%
“…Amphotericin-B is regarded as one of the antifungal agents recommended to be added into selective media for the first isolation of Mycobacterium spp., (19), Campylobacter spp. (20), and Brucella spp.…”
Section: Methodsmentioning
confidence: 99%
“…The isolates were identified using matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) as previously described (16). For the isolation of mycobacteria, the samples were cultured in MGIT tubes (Becton, Dickinson, Pont-De-Claix, France) or on a homemade 5% sheep blood agar (bioMérieux, La Balme-les-Grottes, France) for 2 to 45 days at 32°C or 37°C, as previously described (17). Gram staining was used to ensure the absence of any contaminant organisms in the culture, and standard identification of mycobacteria was performed using MALDI-TOF, as previously described (18).…”
Section: Samplesmentioning
confidence: 99%
“…It has been reported recently that M. tuberculosis can be easily grown on blood agar and chocolate agar (10,11). Moreover, other studies (6)(7)(8)31) have noted that blood agar may be suitable for susceptibility testing of M. tuberculosis.…”
mentioning
confidence: 99%
“…The current recommended Etest procedure for M. tuberculosis is based on Middlebrook 7H11 agar supplemented with oleic acid, albumin, dextrose, and catalase (OADC) (1). In recent years, it has been reported that M. tuberculosis isolates could be grown on blood agar in 1 to 2 weeks (4,10,11,16). In addition, the results of our previous reports have shown that blood agar can be used as an alternative medium for testing M. tuberculosis with isoniazid (IZ), rifampin (RI), streptomycin (SM), and ethambutol (EB) (6-8, 31).…”
mentioning
confidence: 99%
See 1 more Smart Citation